Estimation and Performance analysis of a 15kW Off-Grid Solar PV System - C, Bhuvaneswari; B, Vijay; P, Natarajan (International Journal of Engineering and Technology, 2018)
The primary and most universal measure of all kinds of work by nature is the energy. Coal, Natural gas, Oil and Nuclear energy are net energy yielders and primary sources of energy. The intent of this paper is to assess the performance of 15KW solar power plant installed in Priyadarshini Engineering College (PEC) campus, Vaniyambadi, Vellore District, Tamil Nadu. A 15 kW solar PV plant has been installed to supply electricity to the internet laboratory and library (lighting load). The results obtained from monitoring a 15 KW Solar Photovoltaic system installed on a library roofing of 10m height building. The system was monitored between (July-Sep2016) from 9.30AM to 4.30PM for three days in a week from Monday to Wednesday. The results can be used to provide manufacturers to develop their products and enhance the knowledge in the future in order to improve the design of the off-grid solar photovoltaic system, return of investment during these years. This work focuses on the performance of the solar photovoltaic plant (July-Sep2016) monthly average demand and annual performance parameters, Efficiency, fill factor,capacity Utilisation factor and the characteristics have been plotted in a graph. The graph is drawn between Generated power vs consumed power. The annual yield of the solar photovoltaic plant ranged from 6500-7000 Kwh and performance ratio of 78%. It has capacity Utilisation factor with 6.97%.Â